Analysis Determination of Constitutional Court Decision: President and Vice President Candidate Age - Jessy Chrissensya Anatasya; Sotar Dodo Manurung; Isnaena Chairani; Rachel Elisabeth Sibarani (Problematika Hukum, 2020)
The decision of the Constitutional Court on Law Number 7 of 2017 concerning General Elections: Age Limit for Presidential and Vice Presidential Candidates has become a polemic for Indonesian politics. Constitutional Court decision approving the age limit for the President and Vice President at 35, previously the minimum age was 40 (UU No.7 Article 169 letter q of 2017). In the 1945 Constitution article 24C paragraph 1, the Constitutional Court has no authority to replace and amend laws that the Legislative institution has enacted. This has become a polemic in the election of Indonesian Presidential and Vice Presidential candidates on 14th February 2024. The public considers that the Constitutional Court's decision does not reflect the 5th principle of Pancasila and violates the code of ethics as a judge. This decision of the Constitutional Court changed the Indonesian people's view of the law for the worse because the government easily changed the law.Keywords: Constitution court; Age; President Elections; The Laws